2020
DOI: 10.1002/ehf2.13127
|View full text |Cite
|
Sign up to set email alerts
|

Two year outcome in nonagenarians undergoing percutaneous mitral valve repair

Abstract: Aims Percutaneous mitral valve repair (PMVR) has emerged as standard treatment in selected patients with clinically relevant mitral regurgitation (MR) and increased surgical risk. We aimed to evaluate the safety and clinical outcomes in nonagenarians undergoing PMVR. Methods and results Altogether, 493 patients with severe MR who were treated with PMVR were included in this open-label prospective study and followed up for 2 years. We treated 25 patients with PMVR aged 90 years or above, 185 patients aged 80-89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition, compared with medical therapy alone, M-TEER resulted in a lower rate of hospitalisation due to heart failure within 24 months of follow-up [ 4 ]. We previously demonstrated that the beneficial long-term effects of M-TEER in nonagenarians were comparable to those in younger patients [ 9 ]. These clinical benefits for patients might reduce the costs of healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with medical therapy alone, M-TEER resulted in a lower rate of hospitalisation due to heart failure within 24 months of follow-up [ 4 ]. We previously demonstrated that the beneficial long-term effects of M-TEER in nonagenarians were comparable to those in younger patients [ 9 ]. These clinical benefits for patients might reduce the costs of healthcare systems.…”
Section: Discussionmentioning
confidence: 99%